PEDESTRIAN JALAN GAJAHMADA KOTA SEMARANG: PENILAIAN WALKABILITY INDEX DAN PREFERENSI PEJALAN KAKI - Putri Utoyo, Firani Marinda Putri Utoyo; Kurnianingtyas, Agnesia Putri (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2025)
The Gajahmada Corridor is one of the main thoroughfares that plays a strategic role in the spatial structure of Semarang City. This area functions as a center for commercial, service, and office activities, and serves as a link between important points in the city such as Simpang Lima and Pandanaran Road. The activities of corridor users are highly diverse, including local residents, formal and informal workers, shopping center visitors, and hotel guests. This diversity drives the high intensity of pedestrian activity in the area. Therefore, providing adequate pedestrian facilities is a crucial aspect for enhancing the walkability of the area. This article aims to assess the walkability index along Jalan Gajahmada and evaluate users' perceptions of pedestrian facilities to promote the development of a pedestrian-friendly area as part of efforts to achieve a walkable city, in line with the principles of a green city. The analytical techniques used in this study include assessing the walkability index using the Global Walkability Index (GWI), Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). Primary data was collected through field observations and the distribution of questionnaires to 100 respondents selected via stratified random sampling. The analysis results show that the pedestrian path is in the “good” category with an index score of 70.2 and a user satisfaction level of 70.3, which falls into the “satisfied” category. Supporting facilities and physical barriers are the main concerns because they are considered important but not yet satisfactory. Recommendations for improvement include enhancing crossing facilities, reorganizing space to reduce physical barriers, and providing disability-friendly amenities.